EFFECT OF DUCK MANURE ON THE GROWTH AND YIELD OF SWEET PEAPPER IN ALLUVIAL SOIL - SONI, HAIRI MUZAINI (Jurnal Sains Pertanian Equator, 2018)
(1)Hairi (2)Nurjani (2) Patriani(1)Students of the Faculty of Agriculture and (2)Lecturers of the Agriculture FacultyUniversity Tanjungpura PontianakJalan Prof . Dr. Hadari Nawawie-mail: hairi_vieroo@rocketmail.comABSTRACT This is to determine the effect and dose of duck manure the growth and yield of sweet peapper in alluvial soil. This research was conducted in the Kalimas Village, Sungai Kakap District, Kubu Raya Regency from January 29th,, 2017 to May 29th, 2017. This research used a Completely Randomized Design (CRD), consisting of six treatments and four replications. Each replication consisted of four plant samples. Dosage of duck manure as follows b0 (without treatment), b1 (150 g/polybag), b2 (300 g/polybag), b3 (450 g/polybag), b4 (600 g/polybag) and b5 (750 g/polybag). Variable of the research were on roots volume, plant height, productive branch, dry weight, number of fruit per plant and fruit weight per plant (g). The effect of duck manure impact on roots volume, plant height 8thweek, dry weight, productive branch, the number of fruit plant"™s and fruit weight per plant"™s.Keyword : Alluvial Soil, Manure Duck, Sweet Peppers